2016
DOI: 10.4238/gmr.15027611
|View full text |Cite
|
Sign up to set email alerts
|

GSTP1 Ile105Val and XRCC1 Arg399Gln gene polymorphisms contribute to the clinical outcome of patients with advanced non-small cell lung cancer

Abstract: ABSTRACT. Glutathione S-transferase P1 (GSTP1) and X-ray repair cross-complementing group 1 (XRCC1) genetic variations may influence the efficacy of chemotherapy in various cancers. We investigated the possible roles of GSTP1 Ile105Val and XRCC1 Arg194Trp, and Arg399Gln gene polymorphisms in the prognosis of advanced non-small cell lung carcinoma (NSCLC) patients with cisplatin-based chemotherapy. Between January 2010 and December 2012, this study consecutively recruited 141 patients with advanced NSCLC from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Some studies showed that there was no relationship between them,[ 14 15 ] while other studies have found that the sensitivity of GG wild-type patients to chemotherapy was significantly higher than that of patients carrying at least 1 A allele,[ 16 ] and the response rate of GA or AA genotype carriers was significantly higher than that of patients with type GG. [ 17 18 ] The response rate of chemotherapy in our research was 36.2%, which was similar to that of other studies. However, in our study, the distribution of the XRCC1 G28152A genotype was not balanced.…”
Section: Discussionsupporting
confidence: 90%
“…Some studies showed that there was no relationship between them,[ 14 15 ] while other studies have found that the sensitivity of GG wild-type patients to chemotherapy was significantly higher than that of patients carrying at least 1 A allele,[ 16 ] and the response rate of GA or AA genotype carriers was significantly higher than that of patients with type GG. [ 17 18 ] The response rate of chemotherapy in our research was 36.2%, which was similar to that of other studies. However, in our study, the distribution of the XRCC1 G28152A genotype was not balanced.…”
Section: Discussionsupporting
confidence: 90%
“…The Newcastle-Ottawa Scale (NOS) was used to evaluated the quality of these included studies, based on a scoring system with three components: the selection of the subjects (0–4 points); the comparability of the study groups (0–2 points); the determination of the outcome of interest (treatment response) (0–3 points). The highest NOS score for each publication was 9 points, and in this meta-analysis, two studies had a NOS score of 9 [ 11 , 31 ]; 11 studies had a NOS score of 8 [ 8 – 10 , 12 , 13 , 15 , 16 , 20 , 25 , 26 , 30 ]; eight studies had a NOS score of 7 [ 2 , 7 , 14 , 19 , 21 , 24 , 28 , 29 ]; and two studies had a NOS score of 6 [ 23 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have demonstrated that both environmental and genetic factors are involved in the occurrence and progression of NSCLC (10,16). Increasing evidence suggests that genetic polymorphisms are associated with the risk of NSCLC, as well as inter-individual differences in responses to and toxicity of chemotherapy (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Both the effectiveness and toxicity of chemotherapy vary between patients. Recent studies have suggested that genetic factors play an important role in inter-individual differences in response to chemotherapy, such as the XRCC1, GSTP1 and ERCC1 genes (9)(10)(11). Cheng et al (9) reported that polymorphism in the ERCC1 gene was associated with the response of late-stage patients with NSCLC to cisplatin-based chemotherapy.…”
Section: Introductionmentioning
confidence: 99%